PARTISIPASI POLITIK PEREMPUAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN MINAHASA SELATAN - RAMPISELA, RINI; PANGKEY, MASJE; DENGO, SALMIN (Sam Ratulangi University, 2021)
In this study had a purpose to find out how the political participation of women members of the SouthMinahasa Regency. this research uses a qualitative method. The theory used in this study was the theory ofdecision-making indicators from Robbins and Coulter which included identifying problems, identifyingdecision criteria, developing alternatives, picking an alternative to decisions, carrying an alternative todecisions, carry out the alternative to decisions. the informant in this research is a chairman or member ofthe commission, chairman or legislative agency, chairman or members of the budget agency, and womenmembers of the all amounted to 5 people. Data collection techniques using researchers namely observation,interviews and documentation. The results of this study showed women's political participation members ofthe South Minahasa county representative councils is good if seen from the number of female members whowere able to meet the number of regulations on the minimum of 30% of women in parliament as well asregarding the provisions of women's council participation in holding an important position and has a largeinfluence as the women of the South Minahasa regional representative council in the decision-making andthe implementation of policies. But from 30% of the number of board members who exist were not all able tocontribute directly and affect every decision-making activity is also still the high influence of political partyinterest in carrying out tasks and functions as an legislative member.Keywords : Participation, Political, Women.